A review of the world experience in full-scale testing of existing reinforced concrete structures - O. V. Kabantsev; A. E. Lapshinov (Vestnik MGSU)
Introduction. Domestic and foreign experience of full-scale tests is analyzed. The retrospective of development of standards for conducting full-scale tests in Russia and the USSR is presented. The review of the world regulatory documents regarding the requirements for conducting full-scale tests of structures is carried out, which showed insufficient research of this question both in our country and abroad. The obtained review can be the basis for the development of the national standard of the Russian Federation for conducting full-scale tests.Materials and methods. Analytical review.Results. The state of the issue and the application of stress tests (full-scale tests) in our country, as well as in Germany, the USA, Italy, Canada, Australia, Switzerland and other countries are shown. The minimum requirements for the target test load during testing, the loading mode and acceptance criteria for the experimental assessment of the load-bearing capacity of existing load-bearing structures specified in various standards are given. Specialized criteria for the acceptance of load-bearing structures, such as the permanency ratio and deviation from linearity index, mentioned in individual standards, are analyzed.Conclusions. The similarity of common approaches and the lack of unified requirements for conducting this type of research and evaluating their results are noted. The necessity to develop a national standard of the Russian Federation for full-scale tests of erected reinforced concrete structures is considered.